2004
DOI: 10.1038/sj.eye.6701512
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal triamcinolone as a primary therapy in diabetic macular oedema

Abstract: Purpose To evaluate the effect of intravitreal triamcinolone in eyes with diabetic macular oedema that had no previous laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
4
36
1
1
Order By: Relevance
“…Following Robert Machemer, Gholam Peyman, and others, [1][2][3][4][5][6] intravitreal triamcinolone acetonide has increasingly been used in recent studies as treatment for other intraocular proliferative, oedematous, and neovascular diseases, such as diffuse diabetic macular oedema, [7][8][9][10][11][12][13] central retinal vein occlusion, [14][15][16][17] branch retinal vein occlusion, [18][19][20] chronic uveitis, [21][22][23][24][25] persistent pseudophakic cystoid macular oedema, [26][27][28][29] exudative age-related macular degeneration, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and other diseases. 6 It has remained unclear so far, whether the various ocular disorders differ in their response to intravitreal triamcinolone acetonide in terms of an increase in visual acuity and a rise in intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Following Robert Machemer, Gholam Peyman, and others, [1][2][3][4][5][6] intravitreal triamcinolone acetonide has increasingly been used in recent studies as treatment for other intraocular proliferative, oedematous, and neovascular diseases, such as diffuse diabetic macular oedema, [7][8][9][10][11][12][13] central retinal vein occlusion, [14][15][16][17] branch retinal vein occlusion, [18][19][20] chronic uveitis, [21][22][23][24][25] persistent pseudophakic cystoid macular oedema, [26][27][28][29] exudative age-related macular degeneration, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and other diseases. 6 It has remained unclear so far, whether the various ocular disorders differ in their response to intravitreal triamcinolone acetonide in terms of an increase in visual acuity and a rise in intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Previously, IVTA was considered as an alternative in resistant DME cases, but now some authors suggest it as a first choice treatment without combination. 16,17 Macular PC performed after IVTA was reported to provide significant VA increases at 3 rd and 6 th months, whereas some studies reported insignificant differences. [18][19][20][21] There are few studies evaluated the effects of macular PC added to IVTA on VA.…”
Section: The Effect Of Macular Laser Photocoagulation Onmentioning
confidence: 92%
“…In contrast, two previous studies reported significant VA increases during 6 months with only IVTA application. 16,17 After IVTA, foveal thickness is reduced and retinal transparency is obtained. These effects may increase the effect of macular grid laser on photoreceptors and retinal pigment epithelium which in turn reduces recurrence of DME.…”
Section: Discussionmentioning
confidence: 99%
“…1 However , we would like to highlight several points that may affect the conclusions of their study.…”
mentioning
confidence: 99%
“…We are grateful for Ziahosseini and associates' comments regarding our article. 1 Various studies have shown the benefit of intravitreal triamcinolone acetonide injection in patients with macular oedema secondary to several reasons. [2][3][4][5][6] In our article, the effect of intravitreal triamcinolone in 12 eyes of 12 patients with diabetic macular oedema that had no previous laser treatment was evaluated.…”
mentioning
confidence: 99%